2018
DOI: 10.1002/jclp.22737
|View full text |Cite
|
Sign up to set email alerts
|

Exploring effects of childhood parentification on adult‐depressive symptoms in Korean college students

Abstract: Objective: This study explored parentification dimensions, the age of onset, duration, and family circumstances to better understand the characteristics of parentification and its impact on depressive symptoms among Korean college students.Method: A sample of South Korean college students (N = 316, aged 18-29 years, 66.1% female) rated their childhood parentification experiences and current depressive symptoms.Results: Overall, there were few significant differences in parentification dimensions and depressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Specifically, Asian American and Latin American adolescents indicated they expected to provide support to family, and they exhibited less difference between their perceptions and their parents' values compared to adolescents from a European background. Among Korean college students perceived fairness contributed to associations of parentification and depressive symptoms (Cho & Lee, 2019). Thus, results from these studies allude to the importance of perceptions of children's expectations about their roles in their family.…”
Section: Discussionmentioning
confidence: 77%
“…Specifically, Asian American and Latin American adolescents indicated they expected to provide support to family, and they exhibited less difference between their perceptions and their parents' values compared to adolescents from a European background. Among Korean college students perceived fairness contributed to associations of parentification and depressive symptoms (Cho & Lee, 2019). Thus, results from these studies allude to the importance of perceptions of children's expectations about their roles in their family.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, the parentification experience differs from one person to another, depending on the family's circumstances relinquishing their parental role to their child. The parent's abdication of their role commonly happens in the following: (a) substance use and dependence, (b) environment or contextual factors (e.g., military culture, poverty) and (c) serious medical condition, (d) guardian's poor parenting skills conditions (Cho & Lee, 2019). Indeed, parentification's positive or negative effects depend on whom the parentification is oriented towards either the parent or the sibling and the nature of those relationships (Burton et al, 2018).…”
Section: Parentification Experiences (Definition Types and Domains)mentioning
confidence: 99%
“…On the contrary, Borchet et al (2020) argued that parentification experience increases the child's sense of maturity, self-resilience, empathy, and social understanding (Borchet et al, 2020). The benefits and consequences of parentification depend on age appropriateness and cultural and familial context (Cho & Lee, 2019). Overall, the parentification experience depends on numerous internal and external factors and circumstances to determine its effect on the parentified child.…”
Section: Parentification Experiences (Definition Types and Domains)mentioning
confidence: 99%
“…The gender differences in parentification have been debated, given that findings are inconsistent. Studies that indicate there are no gender differences in parentification can be found (Cho & Lee, 2019;Vulliez-Coady et al, 2013), as well as studies showing that females report higher parentification than males (Byng-Hall, 2008;Schier et al, 2015;Stein et al, 1999;Thomas, 2017) or that males report higher parentification than females do (Arellano et al, 2018;Hooper et al, 2015). At the same time, researchers point out that parentification in boys may be underreported and underestimated as they may be reluctant to admit to carrying out tasks that are considered as not in line with the gender stereotype.…”
Section: Gendermentioning
confidence: 99%